IMPLEMENTASI DAN ANALISIS HONEYPOT BERBASIS COWRIE UNTUK MENDETEKSI SERANGAN SIBER - Aulia, Dhafin Rizky; Rahman, Wahyu Arief; Zhacque, Voully Abdullah (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2025)
The use of the internet in Indonesia has grown rapidly. The Indonesian Internet Service Providers Association (APJII) reported that the number of internet users in Indonesia reached 221,563,479 people in 2024, out of the total population. However, as the number of internet users increases, so do the threats that endanger them. Cybersecurity threats continue to evolve alongside the complexity and sophistication of technologies employed by cybercriminals. In addition to building robust security systems, it is equally important to understand the methods used by attackers to design more effective defense strategies. This is where the concept of honeypots comes into play. A honeypot is a security system designed to mimic vulnerable targets, thereby attracting attackers and revealing the tactics, techniques, and procedures they use. One of the most widely used honeypots is Cowrie. This study utilizes Cowrie as an SSH honeypot to be tested against brute force attacks using Hydra. The results show that Hydra successfully identified 15 username and password combinations from the pre-configured Cowrie system.